2010
DOI: 10.1111/j.1949-8594.2010.00039.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Link between Reformed Teaching Practices and Pupil Learning in Elementary School Mathematics

Abstract: This study examined the classroom practices of beginning elementary school teachers' instruction of mathematics and how it connected to their pupils' learning. The Reformed Teaching Observation Protocol (RTOP) was used to measure the extent to which beginning teachers used reformed teaching practices. As a measure of pupil learning, we utilized assessment scores specific to the mathematics unit observed and correlated them with teachers' RTOP scores. We found that beginning teachers who implemented reformed te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…The analysis described above follows the RTOP analysis described in the RTOP reference manual [47], previous RTOP studies [16,[49][50][51], and other educational studies [52][53][54]. While this method provides a succinct summary of the quantitative data collected during each observation, it overlooks a key feature of this type of data.…”
Section: Alternative Data Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The analysis described above follows the RTOP analysis described in the RTOP reference manual [47], previous RTOP studies [16,[49][50][51], and other educational studies [52][53][54]. While this method provides a succinct summary of the quantitative data collected during each observation, it overlooks a key feature of this type of data.…”
Section: Alternative Data Analysismentioning
confidence: 99%
“…This has been shown to be true at both the K-12 [13][14][15][16][17][18][19] and the college level [20][21][22][23][24][25][26]. Despite the effectiveness of student-centered instruction, research has found this to be a very difficult strategy to teach in-service teachers [13,14] and preservice teachers [27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Οι δάσκαλοι των Μαθηματικών (ή αυτοί που διδάσκουν Μαθηματικά) μπορούν να λειτουργήσουν ως καθοριστικοί διαμεσολαβητές, ώστε να εισαχθούν και να ενσωματωθούν στην εκπαίδευση εκπαιδευτικές μεταρρυθμίσεις, καινοτομίες και τροποποιήσεις στα Προγράμματα Σπουδών (Prestridge & Main, 2018;Serdyukov, 2017;Furinghetti, 1997). Μάλιστα, έχει βρεθεί (Russo & Hopkins, 2019;Gilbert et al, 2014;Jong et al, 2010;Adamson et al, 2003) ότι οι μαθητές, των δασκάλων εκείνων που εφαρμόζουν καινοτομικές πρακτικές διδασκαλίας και υιοθετούν μεταρρυθμίσεις, πετυχαίνουν όχι μόνο υψηλότερους βαθμούς και καλύτερες επιδόσεις σε διάφορα τεστ, αλλά και ωφελούνται μαθησιακά περισσότερο.…”
Section: εισαγωγηunclassified